Combining facelift with SmartLipo 1064-nm system, technique overview and retrospective analysis of 56 patients. (April 2015) - Taghizadeh, Farhan; Leibowitz, Alicia; Ramirez, Patrick; Santos, David
Abstract: Objective: This study reviews novel approach using SmartLipo 1064-nm system with short-flap facelift treatments focusing on 3 specific facial areas and specific target treatment endpoints. A retrospective review of 56 patients undergoing combined treatment is performed. Methods: Fifty-six consecutive patients undergoing SmartLipo with facelift were reviewed using pre-operative photographs as a baseline. The reviewed post-operative photographs were taken at 6 weeks and 6 months. Photographic review was performed by an independent board of physicians on the following scales: Wrinkle Severity Rating Scale, the Global Aesthetic Improvement Scale Assessment, and the Cervicomental Scale. Results: The 53 primary and 3 revision facelift patients included in this study had a mean body mass index of 24.7, and a mean age of 65 years. These patients received an average of 5, 050 joules of energy between three treatment areas which was delivered at 12 Watts and 40 Hz. No major complications were reported, including hematoma and dyspigmentation, even in combined cases with surface lasers. The 6 week and 6 month post-operative photographs showed marked improvements in outcomes in each of the reviewed scales according to the independent board of physicians. Conclusions: The SmartLipo 1064 nm is a safe and effective platform to combine with facelifts.